The future of tableting technology - Abu T. M. Serajuddin (Journal of Excipients and Food Chemicals, 2016)
The availability of a wide array of polymeric excipients, the recent introduction of melt granulation technologies using twin screw extruders, and the interrelationship between excipients and technology will bring major changes in how tablets are formulated and produced in the future. More research is needed to ensure that such innovations are widely applied in the pharmaceutical field.